2017
DOI: 10.1155/2017/7125057
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanisms of Recovery and/or Compensation following Injury

Abstract: Injury due to stroke and traumatic brain injury result in significant long-term effects upon behavioral functioning. One central question to rehabilitation research is whether the nature of behavioral improvement observed is due to recovery or the development of compensatory mechanisms. The nature of functional improvement can be viewed from the perspective of behavioral changes or changes in neuroanatomical plasticity that follows. Research suggests that these changes correspond to each other in a bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 176 publications
1
47
1
1
Order By: Relevance
“…In our own previous study in a normal population of proverb comprehension, we reported that the right precuneus and right supramarginal gyrus are involved in abstract language processing (Yi et al, 2017). In our current study, we observed that transcallosal inhibition (Elkana, Frost, Kramer, Ben-Bashat, & Schweiger, 2013;Griffis et al, 2017;Hartwigsen, 2016;Hartwigsen et al, 2010;Hylin et al, 2017;Lim & Kang, 2015) through the right hemisphere might be reduced because right hemisphere stroke patients show a persistent lesion for about 30 days even when the recovery mechanism has begun. The contralateral homologous cortex may be activated when these patients attempt to comprehend an opaque proverb that requires semantic processing.…”
Section: Abstract Language Processing In Patients With Right Mca Insupporting
confidence: 49%
“…In our own previous study in a normal population of proverb comprehension, we reported that the right precuneus and right supramarginal gyrus are involved in abstract language processing (Yi et al, 2017). In our current study, we observed that transcallosal inhibition (Elkana, Frost, Kramer, Ben-Bashat, & Schweiger, 2013;Griffis et al, 2017;Hartwigsen, 2016;Hartwigsen et al, 2010;Hylin et al, 2017;Lim & Kang, 2015) through the right hemisphere might be reduced because right hemisphere stroke patients show a persistent lesion for about 30 days even when the recovery mechanism has begun. The contralateral homologous cortex may be activated when these patients attempt to comprehend an opaque proverb that requires semantic processing.…”
Section: Abstract Language Processing In Patients With Right Mca Insupporting
confidence: 49%
“…Some principles might be more beneficial early after stroke, whereas others benefit patients with less severe damage. Spontaneous biological recovery and activity-dependent plasticity appear to interact differently at different stages after stroke, which, aside from other factors like severity, predicts recovery (Reinkensmeyer et al, 2016;Hylin et al, 2017). It seems that in acute patients the sensorimotor cortex activity is highly abnormal, and the normalization in activity patterns is linked to better recovery (Schaechter, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative processes within the brain tissue are limited and regulated by tissue environmental properties, which are affected by changes in the physiology of the organism ( Hagg, 2009 ). Neurotrophic factors affect neurogenesis through the condition of the growth of new neurons and the survival of existing ones ( Hylin et al, 2017 ). Traditionally, neurotrophic factors are divided into three protein families: the classic neurotrophin, ligands of Glial Cell Derived Neurotrophic Factor (GDNF), and neuropoietic cytokines.…”
Section: Introductionmentioning
confidence: 99%